Analysis of Sustainable Tourism Management, Tourist Education, and Environmental Awareness on Visit Intention in Ubud, Bali - Adi Pratama, I Wayan; Santi Diwyarthi, Ni Desak Made; Jata, I Wayan; Chintia Pinaria, Ni Wayan; Citrawati, Luh Putu; Kusumarini, Indah (Westscience Press, 2024)
This study examines the impact of sustainable tourism management, tourist education, and environmental awareness on the visiting intentions of tourists in Ubud, Bali. Utilizing a quantitative approach, data were collected from 160 respondents using a Likert scale ranging from 1 to 5. Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) was employed for data analysis to explore the relationships among the variables. The findings indicate that effective sustainable tourism management and heightened environmental awareness significantly enhance tourists' intentions to visit. Additionally, tourist education plays a crucial role in fostering environmental consciousness, further influencing visiting intentions. The results underscore the importance of integrated tourism strategies that prioritize sustainability and education to promote environmentally responsible travel behavior. This research provides valuable insights for policymakers and tourism operators in developing sustainable tourism practices that align with visitors' environmental values.